Trends in AIDS-Defining Opportunistic Illnesses Incidence over 25 Years in Rio de Janeiro, Brazil - Coelho, Lara (Public Library of Science, 2014)
OBJECTIVES: To assess the temporal trends in incidence of AIDS-defining opportunistic illnesses in an urban cohort of a middle-income country. METHODS: HIV infected patients aged ≥18 years at cohort entry were included in this analysis. We calculated incidence rates per 1000 persons-years of observation for the first opportunistic illness presented after cohort enrollment, from 1987 to 2012. Trends for overall and specific opportunistic illnesses were tested and incidence rate ratios for the most recent calendar period were calculated as the ratio between the incidence rate observed in the most recent period of the study (2009–2012) and the incidence rate observed in first period of the study (1987–1990). RESULTS: Overall, 3378 patients were included in this analysis; of which 1119 (33%) patients presented an opportunistic illness during follow up. Incidence rates of all opportunistic illnesses decreased over time, and the overall opportunistic illness incidence rates fell from 295.4/1000 persons-years in 1987–1990 to 34.6/1000 persons-years in 2009–2012. Tuberculosis, esophageal candidiasis, cerebral toxoplasmosis and Pneumocystis jirovecii pneumonia were the most incident opportunistic illnesses in the cohort. Tuberculosis had the highest incidence rate in the study period. The peak in tuberculosis incidence occurred in 1991–1993 (80.8/1000 persons-years). Cerebral toxoplasmosis was the third most incident opportunistic illness in the study, with a peak of incidence of 43.6/1000 persons-year in 1987–1990. CONCLUSIONS: All opportunistic illnesses incidence rates decreased over the years but they still occur in an unacceptable frequency. Tuberculosis co-infection among HIV-infected persists as an important challenge for health care professionals and policy makers in our setting. Impressively high rates of cerebral toxoplasmosis were found suggesting that its incidence among HIV-infected is linked to the high prevalence of Toxoplasma gondii infection in the general population.